Atorvastatin Rapidly Reduces Hepatitis B Viral Load in Combination with Tenofovir: A Prospective Clinical Trial - M. Gharehbeglou; S. Yazdani; K. White; M. R. Haeri; N. Masoumzadeh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective and Aim. Atorvastatin inhibits cholesterol synthesis which is critically important in the formation of the viral envelope and secretion. The efficacy and safety of giving atorvastatin (40 mg/day) as an adjunct to tenofovir in the treatment of hepatitis B (HBV) were assessed. Method. In this single-blind clinical trial, 40 patients with active chronic hepatitis B were randomly allocated to treatment or control groups. The treatment group received the standard treatment for chronic HBV (300 mg tenofovir twice a day) along with 40 mg/day atorvastatin for 12 months, while the control group received a placebo once daily in addition to the standard tenofovir regimen. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and HBV DNA copy numbers were measured at the beginning of the treatment and 1, 3, 6, 9, 12 months later. Results. One month after starting the treatment, the HBV copy number in the atorvastatin + tenofovir-treated group was significantly lower, by 200×, compared with the control group. After three months of the treatment, there was no detectable HBV DNA in 50% of the atorvastatin + tenofovir-treated group compared with 30% in the control group. The half-life of plasma viral load was 2.03 and 3.32 months in the atorvastatin + tenofovir-treated and control groups, respectively. No adverse events due to taking atorvastatin were observed. Conclusions. The combination of atorvastatin with tenofovir increased antiviral activity and led to a faster recovery from viral infection. Therefore, this modality can be recommended as a safe combination therapy for chronic hepatitis B patients.